ANALISIS POLA MAKAN PADA MAHASISWA BARU FAKULTAS OLAHRAGA DAN KESEHATAN UNIVERSITAS PENDIDIKAN INDONESIA - Madeline Magani Azzara Santoso; Nisrina Chaerunnisa; Shanenthly Alnaysha; Tyaswahyu Neema Rasheesa; Frelsa Fairus Addailamy Manoch; Welsi Damayanti (Universitas Al Asyariah Mandar, 2024)
Diet is a general description of how a person or a group of people eats as a whole. It includes the type of food consumed, amount, frequency, and dietary preferences. Diet has a huge impact on a person's health, such as the risk of chronic diseases or the state of nutrition.It is important to pay attention to a balanced diet that includes different types of foods, including fruits, vegetables, proteins, whole grains, and healthy fats. This study aims to analyze related dietary intake in new students of the Faculty of Sports and Health Education at the Indonesian University of Education. Data collection is carried out by qualitative methods in the form of questionnaires. The results of this study show that most of the new students of the Faculty of Sports and Health Education have a regular and healthy diet.